Analisis Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Pekerja Tenun di Desa Ana Engge Kecamatan Kodi Kabupaten Sumba Barat Daya - Jonius Kaka; Andrias U. Roga; Marylin S. Junias; Noorce Ch. Berek (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Work fatigue is described as a condition of feeling tired, exhausted, or drowsy due to prolonged physical and mental workload, ongoing anxiety, added workload from the work environment, or lack of rest/sleep. Work fatigue is the result of prolonged mental and physical labor, which can affect the performance of the workforce and impair their mental alertness. This study aims to analyze the factors associated with work fatigue in cloth weavers in Ana Engge Village, Kodi District, Southwest Sumba Regency. This type of research is an analytic survey with a cross sectional research design. The sample in this study were 67 weavers. The results showed that there was a relationship between the variables of age (p value =0.001), working time (p value=0.010), working period (p value=0.017), work attitude (p value=0.001) with work fatigue in weavers in Ana Engge Village, Kodi District, Southwest Sumba Regency. While nutritional status has no relationship with work fatigue in weavers in Ana Engge Village, Kodi District, Southwest Sumba Regency. It is expected for weavers to pay more attention to their working hours, pay attention to rest periods and also pay attention to work attitudes when doing their work as weavers so as to reduce the risk of fatigue that occurs.